Prioritizing Water Supply Infrastructure Investments in Sri Lanka : An Application of the World Bank Infrastructure Prioritization Framework - Marcelo, Darwin; Saha, Deblina; Raina, Aditi; House, Schuyler (World Bank, Washington, DC, 2018)
Governments are challenged to balance multiple policy goals and make difficult choices when selecting infrastructure projects for public investment, particularly since available funds are often insufficient to implement the full suite of proposals. This paper presents the application of the Infrastructure Prioritization Framework, a systematic, multi-criteria approach to infrastructure project prioritization, to inform the selection of water supply investments in Sri Lanka. A set of 28 proposed water supply projects was prioritized at the request of the National Planning Department of Sri Lanka, based on consideration of multiple goals, including improved water quality and service, network extension, service provision to poor communities, job creation, and sound financial performance. This paper reviews the Infrastructure Prioritization Framework methodology; presents the results of the prioritization exercise, including an expanded sensitivity analysis; and discusses the way forward to apply the Infrastructure Prioritization Framework to inform infrastructure investment decisions.